Teacher’s Teaching Strategies in EFL Class - Anrems Rafika Hayati; Zelvia Liska Afriani; Ali Akbarjono (Yayasan Karinosseff Muda Indonesia, 2021)
Abstract The purpose of this study was to analyze on how the implementation of teaching strategies used by English teacher and the reasons teacher used certain strategies for teaching in SMPN 20 Kota Bengkulu. The subject of this research is English teacher who taught at the first grade in SMPN 20 Kota Bengkulu. The researcher used Roy Killen’s theory to analyze the teaching strategies used by English teacher. The theory of Roy Killen has nine teaching strategies that can be applied by English teacher in teaching and learning process in the classroom. There are direct instruction, discussion, small-group work, co-operative learning, problem solving, research, role play, case study, and writing. The research method used by the researcher was qualitative approach. The techniques of data collection were observation, interview, and documentation. The results of this research show that the teacher used some varieties of teaching strategies which are: direct instruction, discussion, small-group, and role play. The reasons teacher those strategies because those strategies made students more actively on follow the learning process, students could learn together and share their knowledge each other. The teacher used the same strategies for teaching English at first grade, but in term implementation of teaching strategies, the teacher still has difficulties to apply strategies in class during Covid-19 pandemic. Keywords: Teacher, EFL, Teaching Strategies